Effect of a neoprene knee sleeve on performance and muscle activity in men and women during high-intensity, high-volume resistance training - Hatfield, D. L.; Stranieri, A. M.; Vincent, L. M.; Earp, J. E. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was to assess the effects of a commercially available neoprene knee sleeve (KS) on exercise performance and muscle activity during an exhaustive leg press exercise. Twenty resistance-trained individuals, 11 men {21.0 ± 2.2 years; 77.7 ± 8.7 kg; 1 repetition maximum (1RM/body mass [BM]): 0.30 ± 0.04} and 9 women (22.0 ± 3.5 years; 66.1 ± 9.1 kg; 1RM/BM: 0.30 ± 0.04), all subjects (21.5 ± 2.8 years; 72.5 ± 10.5 kg; 1RM/BM: 0.30 ± 0.04), participated in 3 testing sessions. The second and third sessions were performed using a counterbalanced and randomized design in which subjects exercised with (WS) or without (NS) KSs and performed 6 sets of leg press exercise at 80% of 1RM until failure with a 3-minute rest between sets. Number of repetitions, blood lactate (BL), heart rate (HR), rating of perceived exertion (RPE), and peak and average power were recorded after each set. Surface electromyography (EMG) of the right and left vastus lateralis muscles was also recorded to compare muscle activity between conditions. Significance was set at p = 0.05, and values are presented as mean ± SD. No significant differences were observed in the total number of repetitions for all sets (p = 0.3; WS 75.3 ± 33.7, NS 79.8 ± 34.3) and the number of repetitions per set between conditions (p = 0.05) or between men and women. Similarly, no significance differences (p = 0.05) were observed for BL, HR, RPE, or EMG per set between conditions or between men and women. These results suggest that wearing compressive neoprene KSs has no effect on improving performance and associated variables during high-load, high-volume lower-body resistance training.